Liofilização como método de agregar valor ao camarão marinho litopenaeus vannamei - Rocha, Maria Margareth Rolim Martins (2010)
The marine shrimp Litopenaeus vannamei is a worldwide cultivated species, which is responsible for almost all the production of marine aquaculture in Brazil. Besides having a high nutritional value, it is also appreciated by consumers and there is the possibility of elaborating value-added products. The aim of this study is to evaluate the quality of the marine shrimp Litopenaeus vannamei in its lyophilizated form, using samples without pre-cooking and pre-cooked ones, and adding to them the tri and polyphospates and EDTA adictives. Experiences were made in order to determin the most adequate form of the shrimps rehydration and the physico-chemical analysis gathering centesimal composition, water activity, colour, water retention capacity, cholesterol level precision, fatty acids, aminoacids, vitamins, minerals, besides the caloric value, microbiological analysis and sensorial analysis. Lyophilization is a drying process in which the water passes from the solid to the vapor state, without going through the liquid state, leading to a decrease of the water activity and the food can be kept in room temperature. In this study, the rehydration was achieved in 2.5 minutes. The results showed that the Lyophilization process did not cause significant differences for water activity, pH and gain of weight in the rehydration. There has been a significantly different number for CRA in the TPF 5%-PC-L (99.99%). Lipids, proteins and ashes presented numbers with significant difference.The pré-cooked shrimps showed greater intensity of colour (62,05 to 71,06 for the angle a* and 19,22 to 32,59 for the angle b*). Phosphorus and Calcium presented figures between 189,06 and 301, 22 mg/100g. Cholesterol varied from 70,06 to 78,44 mg/100g. Fatty Acids with larger incidence were the mono and poliinsaturated. The aminoacids showed significant oscilations. The result of the sensorial analysis showed that the marine shrimp Litopenaeus vannamei lyophilizated is a product with a added value of great acceptation according to the consumers test.